CORRELATION BETWEEN TIME PERSPECTIVE WITH SUBJECTIVE WELL-BEING AMONG OLDER ADULTS WHO HAD LOSS A SPOUSE - Lestari, Isti Ayu; Hartini, Nurul (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
Individuals aged 60 years experience many changes during the aging process such as physical and social changes. The influence of the aging process often causes various problems, event that has most serious impact on older adults well-being is the death of a spouse. This research aims to determine the correlation between time perspective and subjective well-being among older adults who had loss a spouse. This research used a quantitative approach with Spearman’s rho correlation test analysis. This research was conducted to a sample of 83 widowhood older adults who had loss their spouses. The results shows that there is a relationship between time perspective and subjective well-being with a coefficient on past positive dimensional is 0,697, past negative dimensional is -0,550, present hedonism dimensional is 0,626, present fatalistic dimensional -0,475, and future dimensional is 0,520. Based on the results it can be concluded that each dimension of time perspective is related to subjective well-being.